Network governance in action: the case of Groningen complex decisionmaking in urban regeneration - van Bortel, Gerard (A+BE | Architecture and the Built Environment, 2016)
Theories on network governance constitute a promising approach to a better understanding of complex decision-making and problem-solving. Network theories are increasingly used in housing research. In this paper we present case-study findings on urban regeneration decision-making in Groningen, a medium-sized city in the North of the Netherlands. We used a network governance approach as an analytical framework. Social landlords and local government in Groningen have been collaborating in urban regeneration processes for many years. In 2006 negotiations between these actors on a renewal of the Local Urban Regeneration Covenant ran into difficulties and encountered seemingly insurmountable differences of opinion. These difficulties were largely caused by the increased complexity of the decision-making process, the large number of actors involved and a shift in focus from ‘bricks-and-mortar’ investments to a more balanced approach including social and economic aspects of urban regeneration. In this paper we analyse decision-making on urban regeneration policy in Groningen over the past 10 years. The outcomes of the case study demonstrate the usefulness of the network approach as a framework to analyse decision-making processes. The paper also identifies strategies used by actors in the field to successfully deal with complexities and uncertainties in networks.